Resource, Competition, and the Equilibrium Effects of Innovation Subsidies - Larry D. Qiu; Xu Wei; Mohan Zhou; Yi Zhou (Journal of Economic Behavior and Organization, 2024)
We study the equilibrium effects of innovation subsidies that reduce firms' innovation costs in a monopolistic competition model with firm heterogeneity in innovation capabilities and an industry-level resource constraint. Subsidies change product market competition and resource price, and further affect firms' innovation. We show a counterintuitive result: though subsidies lower innovation costs, high-capability firms may reduce their innovation. This finding implies that the demand curve for innovation investments of certain firms in equilibrium can be locally upward-sloping. We show that at the industry level, both average innovation input and output demonstrate inverted-U shaped responses to increasing subsidies but with differing turning points. Notably, an increase in average innovation input may be accompanied by a decrease in average innovation output. These findings cast doubts on the interpretation of existing empirical evidences on firm and industry responses to innovation subsidies, most of which assume away treatment effect heterogeneity and equilibrium feedbacks.